PWE-043 Polyp Detection Rate And Association With Midazolam Dose. (9th June 2014) - Boyd, J; Harper, C; Lee, L; Chapman, T; Lanzon-Miller, S
Abstract : Introduction: Midazolam is a short acting benzodiazepine that is commonly used for sedation during colonoscopy. There is no standard dose of midazolam, however, British Society of Gastroenterology guidelines suggest a maximum of 5 mg with lower doses for elderly patients. Bowel preparation and endoscopist are factors that have been clearly associated with improved polyp detection during colonoscopy. Anecdotally, colonoscopy in patients who are extremely agitated limits views and leads to a more difficult procedure. Data exploring the relationship between midazolam dose and ability to detect colonic polyps is limited. Methods: A retrospective cohort study of all patients who had undergone colonoscopy at Milton Keynes General hospital between January 2010 and December 2012. Patients were identified from the Endoscopy Unit database and their records were reviewed. Patient details, midazolam dose and diagnosis on colonoscopy were extracted into a standardised form. Results: 6200 patients were included for analysis. The median age was 62 years and 49.4% were male. The mean midazolam dose was 1.9 mg. 16.2% of patients had a low dose of midazolam (<2 mg of midazolam), 74.5% a standard dose of midazolam (2 mg), and 9.3% a high dose (>2 mg). In the low dose cohort, the polyp detection rate (PDR) was 20.8%, in the standard dose, PDR was 26.9% and in the high dose PDR was 16.4%. Rates of agitation were significantly higher in patients who received higher doses of midazolam. When patients with poor bowel preparation were removed from the cohort (n = 5534), PDR was 21.4% in the low dose cohort vs. 27.1% in the standard dose. Conclusion: Adequate sedation of patients during endoscopy is important for patient comfort. In this study we demonstrate that a standard dose of midazolam is associated with a higher polyp detection rate than lower doses. Midazolam has been previously demonstrated to inhibit peristalsis in animal studies by preventing release of 5-HT and this is a probable mechanism for our findings. Limitations arise from the retrospective nature of this study, however, even following stratification of patients by adequacy of bowel prep, PDR remained lower in the low dose midazolam group. Appropriate patient selection for standard dose midazolam is important to avoid respiratory and cardiovascular compromise. Further confirmatory prospective studies are warranted. Disclosure of Interest: None Declared.